Heavy metals content and pollution in tin tailings from Singkep Island, Riau, Indonesia - Irzon, Ronaldo; Syafri, Idrrem; Hutabarat, Johanes; Sendjaja, Purnama; Permanadewi, Sam (Penerbit Universiti Kebangsaan Malaysia, 2018)
Instead of its economic impact, tin mining activities cause environmental problems. The tin occurrence which is related to tin-bearing alteration on S-type Muncung Granite and its mining history in Singkep Island describes in this study. This work assessed the heavy metals concentration in six tin tailings and two soils from Singkep using inductively coupled plasma - mass spectrometry in correlation to environmental hazard. Both primary and placer mining methods applied in tin excavations on the studied area. Concentration tendency of heavy metals in the six studied tailings samples is generally Cr>Pb>As>Ba≈V. The identical heavy metals trend represented by the three samples from Bukit Tumang might reflect a similar primary tailings character. On the other hand, anthropogenic activities and different surrounding rocks caused the dissimilarity of heavy metals pattern on placer wastes. Higher environmental problems are detected on the primary wastes than the placer one, especially arsenic and chrome. Severe arsenic pollution degree is also indicated in the soil sample just outside the mining location at Betong Village. Conservation and amelioration programs are useful in improving the environmental condition on studied locations.